Nonexposure endolaparoscopic full-thickness resection with simple suturing technique - Kim, Chan Gyoo; Yoon, Hong Man; Lee, Jong Yeul; Cho, Soo-Jeong; Kook, Myeong-Cherl; Eom, Bang Wool; Ryu, Keun Won; Kim, Young-Woo; Choi, Il Ju (Endoscopy, 2015)
Background and aim: Current endoscopic full-thickness resection (EFTR) methods are limited by their transmural communication and exposure of tumor to the peritoneum. The aim of this study was to test the feasibility of a new resection technique that does not expose the mucosa to the peritoneum, although it involves an easy and secure suture method, which could be applied in the clinical setting.Methods: The nonexposure endolaparoscopic full-thickness resection with simple suturing technique was performed in four pigs. This new technique includes the steps of laparoscopic seromuscular suturing, which results in inversion of the stomach wall; EFTR of the inverted stomach wall from inside the stomach; and finally, endoscopic mucosal suturing with endoloops and clips.Results: En bloc and complete resections were achieved without adverse events in all pigs. The mean (± standard deviation) operation time was 137.0 ± 28.2 minutes. All pigs survived with no clinical evidence of illness until euthanasia. Gross and microscopic examination of the resection site showed healing without evidence of leakage or infection.Conclusion: The nonexposure endolaparoscopic full-thickness resection with simple suturing technique was feasible in an animal model.